Comparison of Volumetric Change in Objects Printed with LCD and DLP 3D Printers - Sarah Batarseh; Nathan Goldsberry; Carina Handysides; Layla Nemat-Bakhsh; Caleb Valenzuela; Joseph Caruso; Kitichai Rungcharasaeng; Udochukwu Oyoyo (Taylor & Francis Group, 2023)
ABSTRACTBackground Advances in 3D printing are making a significant impact on the future of dentistry. This study evaluated whether the difference in volumetric change of objects printed with the Anycubic and SprintRay 3D printers was clinically or statistically significant.Methods A maxillary left 1st premolar typodont tooth was scanned with a TRIOSTM intra-oral scanner and then printed using AnycubicTM (N = 20) and SprintRayTM (N = 20) 3D printers for a total of 40 printed objects. The printed premolars were scanned with a TRIOSTM scanner after complete cure (T1 or baseline). Subsequent scans were made at 3-, 6-, 24-, and 48-hour after the T1 scan. The scans at different time intervals from each scanner were superimposed, and the volumetric change among the scans was analyzed and recorded using a matching software (Geomagic WRAP®). The volumetric changes at different time intervals for both printers were analyzed using a Mann-Whitney U test α = 0.05.Results The mean volumetric change of the printed teeth from both AnycubicTM (−1.28 mm3) and SprintRayTM (−3.06 mm3) were minimal and not statistically significantly different from each other at any time points (p > .05).Conclusions Both printers showed no clinically significant volumetric change. Although not a statistically significant difference, the AnycubicTM printed objects demonstrated greater stability in comparison to the SprintRayTM printed objects.Practical Implications This study showed that clinically acceptable accuracy/outcomes of printed objects can be achieved with a lower-cost option, such as an AnycubicTM 3D printer.